The role of Akt (protein kinase B) and protein kinase C in ischemia–reperfusion injury. (2nd April 2016) - Zhao, Ethan Y.; Efendizade, Aslan; Cai, Lipeng; Ding, Yuchuan
Abstract : Stroke is a leading cause of long-term disability and death in the United States. Currently, tissue plasminogen activator (tPA), is the only Food and Drug Administration-approved treatment for acute ischemic stroke. However, the use of tPA is restricted to a small subset of acute stroke patients due to its limited 3-h therapeutic time window. Given the limited therapeutic options at present and the multi-factorial progression of ischemic stroke, emphasis has been placed on the discovery and use of combination therapies aimed at various molecular targets contributing to ischemic cell death. Protein kinase C (PKC) and Akt (protein kinase B) are serine/threonine kinases that play a critical role in mediating ischemic–reperfusion injury and cellular growth and survival, respectively. The present review will examine the role of PKC and Akt in the cellular response to ischemic–reperfusion injury.